Solid polymer electrolyte membrane, membrane electrode assembly, and solid polymer water electrolysis device
By using acid-type sulfonate perfluoropolymer with hydrogen permeability coefficient and membrane resistance value within a specific range as solid polymer electrolyte membrane, the low electrolytic voltage and poor hydrogen recovery efficiency in solid polymer hydroelectric electrolytic devices are solved. The problem of this method has achieved a reduction in electrolytic voltage and an improvement in hydrogen recovery efficiency, and is suitable for various types of solid polymer hydroelectric electrolytic devices.
Patent Information
- Application Number
- CN202080017013.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-02-28
- Filing Date
- 2020-02-28
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2040-02-28
AI Technical Summary
The existing solid polymer hydroelectric electrolytic devices have low electrolytic voltage and poor hydrogen recovery efficiency. The solid polymer electrolyte membrane is prone to breakage during operation, so it cannot be suitable for all types of solid polymer hydroelectric electrolytic devices.
The acid-type sulfonic acid perfluoropolymer with hydrogen permeability coefficient below the specified value and the membrane resistance value is within a specific range as the solid polymer electrolyte membrane, and is used to manufacture a membrane electrode bond with low electrolytic voltage and excellent hydrogen recovery efficiency. and solid polymer type water electrolytic device.
The electrolytic voltage reduction and hydrogen recovery efficiency in solid polymer water electrolytic devices are achieved, and the service life of the electrolyte membrane is extended. It is suitable for various types of solid polymer water electrolytic devices.
Smart Images

Figure CN113518838B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a solid polymer electrolyte membrane, a membrane electrode assembly and a solid polymer water electrolysis device. Background Art
[0002] The solid polymer electrolyte membrane included in the membrane electrode assembly is obtained by, for example, forming a polymer having an acidic sulfonic acid group into a film. As such a polymer having an acidic sulfonic acid group, a perfluoropolymer having a unit represented by -[CF2-CF(OCF2CF2SO3H)]- is disclosed in the examples of Patent Document 1.
[0003] The membrane electrode assembly including the solid polymer electrolyte membrane can be used in various applications. For example, in addition to being used in the solid polymer fuel cell described in Patent Document 1, it can also be used in the solid polymer water electrolysis device described in Patent Document 2.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2005-082749
[0007] Patent Document 2: Japanese Patent Application Laid-Open No. 11-021687 Summary of the invention
[0008] Problem that the invention aims to solve
[0009] In recent years, there has been a demand for further improvement in the performance of solid polymer water electrolysis devices. Specifically, low electrolysis voltage and excellent recovery efficiency of hydrogen generated at the cathode have been sought.
[0010] In addition, in the solid polymer water electrolysis device, a large pressure is applied to the solid polymer electrolyte membrane separating the anode chamber and the cathode chamber. Therefore, during the operation of the solid polymer water electrolysis device, the solid polymer electrolyte membrane is damaged, and depending on the type of the solid polymer electrolyte membrane, it is sometimes not suitable for the solid polymer water electrolysis device.
[0011] The present inventors evaluated a solid polymer electrolyte membrane containing the perfluoropolymer described in Patent Document 1 as an electrolyte and found that there is room for improvement in at least one of the electrolysis voltage and hydrogen recovery efficiency of a solid polymer water electrolysis device.
[0012] In view of the above-mentioned actual situation, the present invention aims to provide a solid polymer electrolyte membrane that can be applied to a solid polymer water electrolysis device and can manufacture a solid polymer water electrolysis device with low electrolysis voltage and excellent hydrogen recovery efficiency, as well as a membrane electrode assembly and a solid polymer water electrolysis device obtained using the membrane electrode assembly.
[0013] Solutions for solving problems
[0014] The inventors of the present invention have conducted in-depth research on the above-mentioned issues and found that if a solid polymer electrolyte membrane including a polymer electrolyte membrane having a hydrogen permeability coefficient below a specified value and a membrane resistance value within a specified range is used, it can be applied to a solid polymer water electrolysis device, and a solid polymer water electrolysis device with a low electrolysis voltage and excellent hydrogen recovery efficiency can be manufactured, thereby completing the present invention.
[0015] That is, the present inventors have found that the above-mentioned problems can be solved by the following configuration.
[0016] [1] A solid polymer electrolyte membrane, characterized in that it contains a polymer electrolyte, wherein the polymer electrolyte has a hydrogen permeability coefficient of 2.4×10 -9 cm 3 cm / (s cm 2 cmHg) or less,
[0017] The membrane resistance of the solid polymer electrolyte membrane is 50 to 150 mΩ·cm under the conditions of a temperature of 80° C. and a relative humidity of 50%. 2 .
[0018] [2] The solid polymer electrolyte membrane according to [1], wherein the polymer electrolyte is a perfluoropolymer having an acidic sulfonic acid group.
[0019] [3] The polymer electrolyte membrane according to [2], wherein the perfluoropolymer comprises a perfluoromonomer unit, and the perfluoromonomer unit comprises at least one unit selected from the group consisting of a perfluorovinyl ether unit and a perfluoroallyl ether unit.
[0020] [4] A solid polymer electrolyte membrane according to [2] or [3], wherein the perfluoropolymer does not substantially contain at least one unit selected from the group consisting of a unit having a halogen atom other than a fluorine atom, a unit having a ring structure, and a unit having a cross-linked structure formed by a covalent bond.
[0021] [5] The solid polymer electrolyte membrane according to [4], wherein the perfluoroallyl ether unit is a unit represented by the formula A-1 described below. In the formula A-1 described below, R F1 and RF2 Each is independently a perfluoroalkylene group having 1 to 3 carbon atoms.
[0022] [6] The polymer electrolyte membrane according to any one of [3] to [5], wherein the perfluoromonomer unit further includes a tetrafluoroethylene unit.
[0023] [7] The solid polymer electrolyte membrane according to any one of [1] to [6], wherein the ion exchange capacity of the polymer electrolyte is 1.4 to 2.5 milliequivalents / g dry resin.
[0024] [8] A membrane electrode assembly, characterized in that it comprises: an anode having a catalyst layer, a cathode having a catalyst layer, and a solid polymer electrolyte membrane according to any one of [1] to [7] arranged between the anode and the cathode.
[0025] [9] A solid polymer water electrolysis device, characterized in that it comprises the membrane electrode assembly of [8].
[0026] Effects of the Invention
[0027] According to the present invention, a solid polymer electrolyte membrane that can be applied to a solid polymer water electrolysis device and can manufacture a solid polymer water electrolysis device with low electrolysis voltage and excellent hydrogen recovery efficiency, as well as a membrane electrode assembly and a solid polymer water electrolysis device obtained using the membrane electrolyte membrane can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a schematic cross-sectional view showing an example of the membrane electrode assembly of the present invention. DETAILED DESCRIPTION
[0029] The following definitions of terms apply throughout the specification and claims unless otherwise specified.
[0030] The "ion exchange group" refers to a group that can exchange at least a part of ions contained in the group for other ions, and examples thereof include the following sulfonic acid type functional group and carboxylic acid type functional group.
[0031] "Sulfonic acid functional groups" are acidic sulfonic acid groups (-SO3H) and salt-type sulfonic acid groups (-SO3M 2 Among them, M 2 A general term for alkali metal or quaternary ammonium cations.
[0032] "Carboxylic acid functional groups" are acidic carboxylic acid groups (-COOH) and salt-type carboxylic acid groups (-COOM 1 Among them, M 1 A general term for alkali metal or quaternary ammonium cations.
[0033] “Substantially containing no unit” means that the content of the unit is 1 mol% or less based on all units of the polymer containing the unit.
[0034] The "unit" in a polymer refers to an atomic group derived from one molecule of a monomer and formed by polymerization of the monomer. The unit may be an atomic group directly formed by a polymerization reaction, or may be an atomic group of another structure converted by treating the polymer obtained by the polymerization reaction. It should be noted that the structural unit derived from each monomer is sometimes recorded by a name in which the monomer name is annotated with "unit".
[0035] The unit represented by the formula A-1 is referred to as unit A-1. The units represented by other formulae are described similarly.
[0036] The compound represented by formula 1-1 is referred to as compound 1-1. The compounds represented by other formulae are described in the same manner.
[0037] [Solid polymer electrolyte membrane]
[0038] The solid polymer electrolyte membrane (hereinafter also referred to as "electrolyte membrane") of the present invention comprises a polymer electrolyte having a hydrogen permeability coefficient of 2.4×10 -9 cm 3 cm / (s cm 2 ·cmHg), the membrane resistance of the solid polymer electrolyte membrane is 50 to 150 mΩ·cm under the conditions of temperature 80°C and relative humidity 50%. 2 .
[0039] The electrolyte membrane of the present invention can produce a solid polymer water electrolysis device having a low electrolysis voltage and excellent hydrogen recovery efficiency. The detailed reason for this is not clear, but it is presumed to be due to the following reasons.
[0040] The solid polymer water electrolysis device generates oxygen on the anode side and hydrogen on the cathode side. If the hydrogen generated on the cathode side passes through the electrolyte membrane and moves to the anode side (so-called hydrogen crossover), the hydrogen recovery efficiency of the solid polymer water electrolysis device decreases.
[0041] In view of this problem, the present inventors have found that the use of an electrolyte membrane containing a polymer electrolyte having a hydrogen permeability coefficient of a predetermined value or less can suppress hydrogen crossover, resulting in a solid polymer water electrolysis device having excellent hydrogen recovery efficiency.
[0042] On the other hand, the present inventors have found that although the electrolysis voltage of the solid polymer water electrolysis device can be slightly reduced by setting the hydrogen permeability coefficient to a predetermined value or less, there is still room for improvement.
[0043] In response to this problem, the present inventors have found that if an electrolyte membrane having a membrane resistance value within a specified range is used, a solid polymer water electrolysis device with a low electrolysis voltage can be obtained. That is, it can be inferred that the effect obtained by setting the hydrogen permeability coefficient of the polymer electrolyte to a specified value or less and the effect obtained by using an electrolyte membrane having a membrane resistance value within a specified range work synergistically, thereby obtaining a solid polymer water electrolysis device with a sufficiently low electrolysis voltage.
[0044] <Polymer Electrolyte>
[0045] The polymer electrolyte is not particularly limited as long as it is an electrolyte formed by a polymer whose hydrogen permeability coefficient satisfies the range described below. From the viewpoint of being able to further reduce the electrolysis voltage of the solid polymer water electrolysis device and having a better hydrogen recovery efficiency, a perfluoropolymer having an acidic sulfonic acid group (hereinafter also referred to as "polymer H") is preferred.
[0046] From the viewpoint of excellent durability of the electrolyte membrane, the polymer H preferably contains a perfluoromonomer unit.
[0047] From the viewpoint of being able to further reduce the electrolysis voltage of the solid polymer water electrolysis device, the perfluoromonomer unit preferably contains at least one unit selected from the group consisting of perfluorovinyl ether units and perfluoroallyl ether units (hereinafter also referred to as "unit A").
[0048] The unit A may contain one or both of a perfluorovinyl ether unit and a perfluoroallyl ether unit, but preferably contains a perfluoroallyl ether unit, and particularly preferably a perfluoroallyl ether unit, from the viewpoint of easy synthesis.
[0049] From the viewpoint of lowering the membrane resistance of the electrolyte membrane and further reducing the electrolysis voltage of the solid polymer water electrolysis device, the unit contained in unit A preferably has an ion exchange group, more preferably a sulfonic acid functional group, and particularly preferably an acidic sulfonic acid group.
[0050] When each unit contained in unit A has an ion exchange group, from the viewpoint of lowering the membrane resistance of the electrolyte membrane and being able to further reduce the electrolysis voltage of the solid polymer water electrolysis device, the number of ion exchange groups in each unit is preferably 2 or more, and from the viewpoint of easy synthesis, 2 is particularly preferred.
[0051] The perfluoroallyl ether unit is preferably unit A-1 from the viewpoint of easily obtaining a polymer electrolyte having a hydrogen gas permeability coefficient within the range described below and a membrane resistance value within the range described below when formed into a membrane.
[0052]
[0053] The perfluorovinyl ether unit is preferably unit A-2 or unit A-3 from the viewpoint of easily obtaining a polymer electrolyte having a hydrogen permeability coefficient within the range described below and a membrane resistance value within the range described below when formed into a membrane.
[0054]
[0055] In Formula A-1 to Formula A-3, R F1 and R F2 Each is independently a perfluoroalkylene group having 1 to 3 carbon atoms.
[0056] As R F1 and R F2 Specific examples include -CF2-, -CF2CF2-, -CF(CF3)-, -CF2CF2CF2-, -CF(CF2CF3)-, -CF(CF3)CF2-, -CF2CF(CF3)-, and -C(CF3)(CF3)-.
[0057] From the viewpoint of low raw material cost, easy production, and the ability to further increase the ion exchange capacity of polymer H, R F1 and R F2 Each independently is preferably a perfluoroalkylene group having 1 or 2 carbon atoms. In the case of 2 carbon atoms, a straight chain is preferred. Specifically, -CF2-, -CF2CF2- or -CF(CF3)- is preferred, -CF2- or -CF2CF2- is more preferred, and -CF2- is particularly preferred.
[0058] In formula A-2, R F3 It is a perfluoroalkylene group having 1 to 6 carbon atoms.
[0059] As R F3 Specific examples include -CF2-, -CF2CF2-, -CF(CF3)-, -CF2CF2CF2-, -CF(CF2CF3)-, -CF(CF3)CF2-, -CF2CF(CF3)-, -C(CF3)(CF3)-, and -CF2CF(CF3)OCF2CF(CF3)-.
[0060] From the viewpoint of low raw material cost, easy production, and the ability to further increase the ion exchange capacity of polymer H, R F3It is preferably a perfluoroalkylene group having 1 to 3 carbon atoms. Specifically, it is preferably -CF2-, -CF2CF2- or -CF2CF(CF3)-, and particularly preferably -CF2CF(CF3)-.
[0061] In formula A-2, m is 0 or 1.
[0062] The perfluoro monomer unit may contain units other than the unit A. As the units other than the unit A, there can be mentioned perfluoro monomer units having no ion exchange group and its precursor group.
[0063] Specific examples of the perfluoromonomer unit having no ion exchange group and its precursor group include tetrafluoroethylene (hereinafter also referred to as "TFE") unit and hexafluoropropylene unit. From the viewpoint of excellent strength of the electrolyte membrane, the TFE unit is preferred.
[0064] From the viewpoint of easily setting the ion exchange capacity and hydrogen permeability coefficient of the polymer electrolyte within the ranges described below and from the viewpoint of easily obtaining an electrolyte membrane having a membrane resistance value within the range described below, the lower limit of the content of unit A is preferably 7 mol %, more preferably 8 mol %, and particularly preferably 9 mol % relative to all units in polymer H.
[0065] From the viewpoint of excellent strength of the electrolyte membrane, the upper limit of the content of the units A is preferably 45 mol % based on all units in the polymer H, more preferably 36 mol %, and particularly preferably 22 mol %.
[0066] When a perfluoromonomer unit having no ion exchange group and its precursor group is contained, its content is preferably 55 to 93 mol%, more preferably 65 to 92 mol%, and particularly preferably 78 to 91 mol% based on all units in the polymer H. These contents are particularly suitable when the perfluoromonomer unit is a TFE unit.
[0067] The polymer H preferably does not substantially contain a unit having a halogen atom other than a fluorine atom (hereinafter also referred to as "unit X1"). Thus, a chain transfer reaction is less likely to occur when polymerizing the monomer to produce the polymer H, and the amount of oligomers produced during production is small.
[0068] Specific examples of the unit X1 include a chlorotrifluoroethylene unit, a bromotrifluoroethylene unit, an iodotrifluoroethylene unit, and a dichlorodifluoroethylene unit.
[0069] The polymer H substantially does not contain the unit X1 means that the content of the unit X1 is 1 mol% or less relative to all units in the polymer H, and preferably does not contain the unit X1 (0 mol%).
[0070] The polymer H preferably does not substantially contain a unit having a ring structure (hereinafter also referred to as "unit X2"), thereby preventing the polymer H from becoming brittle and increasing the toughness of the polymer H. Therefore, the electrolyte membrane obtained using the polymer H has excellent mechanical strength.
[0071] Examples of the ring structure include an aliphatic hydrocarbon ring, an aliphatic heterocyclic ring, an aromatic hydrocarbon ring, and an aromatic heterocyclic ring. The ring structure may be present in the main chain or in the side chain.
[0072] Specific examples of the unit X2 include units having a cyclic ether structure described in Japanese Patent Nos. 4,997,968 and 5,454,592.
[0073] The polymer H substantially does not contain the unit X2, which means the same as the unit X1, and preferably does not contain it (0 mol%).
[0074] The polymer H preferably does not substantially contain a unit having a cross-linked structure formed by a covalent bond (hereinafter also referred to as "unit X3"). As a result, the polymer H is easily dissolved or dispersed in a liquid medium, and therefore, when a liquid composition containing the polymer H and the liquid medium is used to form an electrolyte membrane, the thickness of the electrolyte membrane can be easily adjusted.
[0075] The crosslinked structure formed by covalent bonds refers to a structure obtained by polymerizing a monomer having a crosslinkable group (such as a vinyl group and a perfluorovinyl group) that can be crosslinked by covalent bonds, and then crosslinking the crosslinkable groups by covalent bonds.
[0076] As specific examples of unit X3, there can be listed units having the following structures: a structure obtained by polymerizing compounds of formulas 8 to 15 (compounds having two cross-linking groups) described in Japanese Patent Gazette No. 2001-176524, and then cross-linking the cross-linking groups not used in the polymerization via covalent bonds; or a structure obtained by cross-linking a monomer having a cross-linking group that can be cross-linked via covalent bonds simultaneously with the polymerization reaction.
[0077] The polymer H substantially does not contain the unit X3, which means the same as the unit X1, and preferably does not contain it (0 mol%).
[0078] (Method for producing polymer electrolyte)
[0079] As an example of a method for producing a polymer electrolyte, a method for producing the above-mentioned polymer H will be described as an example.
[0080] An example of a method for producing polymer H is as follows: a precursor polymer (hereinafter also referred to as "polymer F") in which the acidic sulfonic acid group in polymer H becomes a precursor group (specifically, a group represented by -SO2F) is converted into an acidic sulfonic acid group (-SO3- H + ) method.
[0081] As a specific example of the method of converting the group represented by -SO2F belonging to the precursor group into an acid-type sulfonic acid group, there is listed a method of hydrolyzing the group represented by -SO2F of polymer F to form a salt-type sulfonic acid group, and converting the salt-type sulfonic acid group into an acid-type sulfonic acid group.
[0082] The polymer F is preferably a perfluoropolymer containing a perfluoro monomer unit and having a group represented by -SO2F.
[0083] The perfluoromonomer unit in the polymer F preferably contains at least one unit selected from the group consisting of a perfluorovinyl ether unit and a perfluoroallyl ether unit (hereinafter also simply referred to as "unit a").
[0084] The unit a may contain one or both of a perfluorovinyl ether unit and a perfluoroallyl ether unit, but preferably contains a perfluoroallyl ether unit, and particularly preferably a perfluoroallyl ether unit, from the viewpoint of easy synthesis.
[0085] The unit contained in unit a may or may not have a precursor group having an ion exchange group. It is preferably a precursor group having an ion exchange group, and particularly preferably a precursor group having a sulfonic acid type functional group (specifically a group represented by -SO2F).
[0086] Specific examples of the perfluorovinyl ether unit in the unit a include units obtained by converting the acidic sulfonic acid group of the perfluorovinyl ether unit in the above-mentioned unit A into a group represented by -SO2F.
[0087] The perfluoroallyl ether unit in the unit a is preferably the unit a-1.
[0088]
[0089] R in formula a-1 F1 and R F2 Respectively with R in formula A-1 F1 and R F2 have the same meaning.
[0090] The perfluoromonomer unit in the unit a may contain units other than the unit a. Specific examples of the units other than the unit a include perfluoromonomer units having no ion exchange group and its precursor group.
[0091] Specific examples of the perfluoromonomer unit having no ion exchange group and its precursor group are the same as those of the polymer H.
[0092] The content of each unit in the polymer F is preferably the same as the content of each unit in the polymer H.
[0093] The polymer F preferably contains substantially no at least one unit selected from the group consisting of a unit having a halogen atom other than a fluorine atom, a unit having a ring structure, and a unit having a crosslinked structure formed by a covalent bond, and particularly preferably contains substantially no all of these units.
[0094] Specific examples of the unit having a halogen atom other than a fluorine atom, the unit having a ring structure, and the unit having a crosslinked structure formed by a covalent bond are the same as those for the polymer H.
[0095] In addition, the phrase “substantially free” has the same meaning as that of the case of the polymer H.
[0096] The capacity flow rate value (hereinafter also referred to as "TQ value") of polymer F is preferably 220°C or more, more preferably 225 to 360°C, and further preferably 230 to 350°C. If the TQ value is above the lower limit, a polymer H having a sufficient molecular weight can be obtained, and therefore, the strength of the electrolyte membrane is excellent. If the TQ value is below the upper limit, the solubility or dispersibility of polymer H relative to the liquid medium is improved, and therefore, it is easy to prepare a liquid composition. The TQ value is an indicator of the molecular weight of polymer F.
[0097] The "TQ value" of the polymer F can be determined by the method described in the Examples section below.
[0098] <Physical properties>
[0099] The hydrogen permeability coefficient of the polymer electrolyte at 80°C and 10% relative humidity is 2.4×10 -9 cm 3 cm / (s cm 2 cmHg) or less, preferably 2.2×10 -9 cm 3 cm / (s cm 2 cmHg) or less, more preferably 2.0×10 -9 cm 3 cm / (s cm 2 cmHg) or less, particularly preferably 1.8×10 -9 cm 3 cm / (s cm 2 When the hydrogen permeability coefficient is below the upper limit value, the occurrence of hydrogen crossover can be suppressed.
[0100] From the viewpoint of being able to reduce the resistance value of the electrolyte membrane and further reduce the electrolysis voltage of the solid polymer water electrolysis device, the hydrogen permeability coefficient of the polymer electrolyte under the conditions of a temperature of 80°C and a relative humidity of 10% is preferably 1.0×10-12 cm 3 cm / (s cm 2 cmHg) or more, particularly preferably 1.0×10 -11 cm 3 cm / (s cm 2 ·cmHg) or above.
[0101] The “hydrogen gas permeability coefficient” of the polymer electrolyte was determined by using a 25 μm-thick membrane formed of the polymer electrolyte and by the method described in the later-described Example section.
[0102] The ion exchange capacity of the polymer electrolyte is preferably 1.4 to 2.5 milliequivalents / gram of dry resin, more preferably 1.6 to 2.4 milliequivalents / gram of dry resin, and particularly preferably 1.8 to 2.3 milliequivalents / gram of dry resin. If the ion exchange capacity of the polymer electrolyte is above the lower limit, the resistance of the electrolyte membrane obtained using it can be further reduced, and as a result, the electrolysis voltage of the solid polymer water electrolysis device can be further reduced. If the ion exchange capacity of the polymer electrolyte is below the upper limit, the strength when made into an electrolyte membrane is excellent.
[0103] The "ion exchange capacity" of the polymer electrolyte can be determined by the method described in the Examples section below.
[0104] The water content (by mass) of the polymer electrolyte is preferably 30 to 300%, particularly preferably 40 to 200%. If it is above the lower limit, the ion conductivity of the electrolyte membrane becomes higher, so the electrolysis voltage of the solid polymer water electrolysis device can be further reduced. If it is below the upper limit, the electrolyte membrane will not swell excessively due to water, so the mechanical strength of the electrolyte membrane is excellent.
[0105] The “water content” of the polymer electrolyte was determined by the method described in the later-described Example section using a 25 μm-thick film formed of the polymer electrolyte.
[0106] The membrane resistance of the electrolyte membrane under the conditions of temperature 80°C and relative humidity 50% is 50 to 150 mΩ·cm 2 .
[0107] From the viewpoint of improving membrane strength and further suppressing hydrogen crossover in the solid polymer water electrolysis device, the lower limit of the membrane resistance is preferably 65 mΩ·cm 2 , more preferably 75 mΩ·cm 2 .
[0108] From the viewpoint of being able to further reduce the electrolysis voltage of the solid polymer water electrolysis device, the upper limit of the membrane resistance value is preferably 135 mΩ·cm 2, more preferably 125 mΩ·cm 2 .
[0109] The "membrane resistance value" of the electrolyte membrane is obtained by the method described in the section of Examples described later.
[0110] The conductivity of the electrolyte membrane under the conditions of a temperature of 80°C and a relative humidity of 50% is preferably 0.08 to 0.16 S / cm, particularly preferably 0.1 to 0.15 S / cm. If it is above the lower limit, the electrolysis voltage of the solid polymer water electrolysis device can be further reduced. If it is below the upper limit, the mechanical durability of the electrolyte membrane is sufficient.
[0111] The "conductivity" of the electrolyte membrane is determined by the method described in the later-described Example section.
[0112] The thickness of the electrolyte membrane is preferably 50 to 200 μm, particularly preferably 70 to 130 μm. If it is above the lower limit, the membrane strength of the electrolyte membrane can be increased, and the crossover of hydrogen can be further suppressed. If it is below the upper limit, the resistance value of the electrolyte membrane can be further reduced, and therefore, the electrolysis voltage of the solid polymer water electrolysis device can be further reduced.
[0113] The film thickness of the electrolyte membrane refers to the average film thickness determined by the method described in the Examples section below.
[0114] <Other Materials>
[0115] The electrolyte membrane may be reinforced with a reinforcing material. Specific examples of the reinforcing material include porous bodies, fibers, woven fabrics, and nonwoven fabrics.
[0116] The reinforcing material is preferably composed of a material selected from the group consisting of polytetrafluoroethylene (hereinafter also referred to as "PTFE"), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (hereinafter also referred to as "PFA"), polyetheretherketone (hereinafter also referred to as "PEEK") and polyphenylene sulfide (hereinafter also referred to as "PPS").
[0117] In order to further improve durability, the electrolyte membrane may contain one or more metals, metal compounds or metal ions selected from the group consisting of cerium and manganese. Cerium and manganese decompose hydrogen peroxide, which is a causative substance that causes degradation of the electrolyte membrane.
[0118] The electrolyte membrane may contain silicon dioxide or a heteropoly acid (eg, zirconium phosphate, phosphomolybdic acid, phosphotungstic acid) as a moisture retaining agent for preventing drying.
[0119] <Purpose>
[0120] The electrolyte membrane can be suitably used as a solid polymer electrolyte membrane of a solid polymer water electrolysis device.
[0121] <Method for producing electrolyte membrane>
[0122] As an example of a method for producing an electrolyte membrane, there is mentioned a method (casting method) in which a liquid composition described later is applied to the surface of a substrate film or a catalyst layer and then dried.
[0123] As an example of a production method when the electrolyte membrane includes a reinforcing material, there is a method of impregnating the reinforcing material with a liquid composition described later and drying the reinforcing material.
[0124] In order to stabilize the electrolyte membrane, it is preferred to perform heat treatment. The heat treatment temperature also varies depending on the type of polymer electrolyte, and is preferably 130 to 200°C. If the heat treatment temperature is 130°C or higher, the water content of the polymer electrolyte becomes appropriate. If the heat treatment temperature is 200°C or lower, the thermal decomposition of the sulfonic acid group can be suppressed, and the excellent conductivity of the electrolyte membrane can be maintained.
[0125] The electrolyte membrane may be treated with an aqueous hydrogen peroxide solution as necessary.
[0126] (Liquid composition)
[0127] The liquid composition preferably contains a polymer electrolyte and a liquid medium. The polymer electrolyte in the liquid composition may be dispersed in the liquid medium or may be dissolved in the liquid medium.
[0128] Specific examples of the liquid medium include water and organic solvents. The liquid medium may be water alone, an organic solvent alone, or a mixed solvent of water and an organic solvent. A mixed solvent of water and an organic solvent is preferably used.
[0129] When water is included as the liquid medium, the dispersibility or solubility of the polymer electrolyte in the liquid medium is likely to be improved. When an organic solvent is included as the liquid medium, an electrolyte membrane that is not easily broken is likely to be obtained.
[0130] As the organic solvent, alcohols having 1 to 4 carbon atoms are preferred from the viewpoint of easily obtaining an electrolyte membrane that is less prone to rupture.
[0131] Examples of the alcohol having 1 to 4 carbon atoms include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2,2,2-trifluoroethanol, 2,2,3,3,3-pentafluoro-1-propanol, 2,2,3,3-tetrafluoro-1-propanol, 1,1,1,3,3,3-hexafluoro-2-propanol and 3,3,3-trifluoro-1-propanol.
[0132] The organic solvent may be used alone or in combination of two or more.
[0133] When the liquid medium is a mixed solvent of water and an organic solvent, the content of water is preferably 10 to 99% by mass, particularly preferably 20 to 99% by mass, based on the total mass of the liquid medium.
[0134] When the liquid medium is a mixed solvent of water and an organic solvent, the content of the organic solvent is preferably 1 to 90% by mass, particularly preferably 1 to 80% by mass.
[0135] When the content of water and the organic solvent is within the above range, an electrolyte membrane which is excellent in dispersibility or solubility of the polymer electrolyte in the liquid medium and is not easily broken can be easily obtained.
[0136] The content of the polymer electrolyte is preferably 1 to 50% by mass, particularly preferably 3 to 30% by mass, relative to the total mass of the liquid composition. If it is above the lower limit of the above range, a film with a thickness can be stably obtained during film formation. If it is below the upper limit of the above range, the viscosity of the liquid composition becomes appropriate.
[0137] In order to further improve the durability of the electrolyte membrane produced from the liquid composition, the liquid composition may contain one or more metals, metal compounds or metal ions selected from the group consisting of cerium and manganese.
[0138] [Membrane Electrode Assembly]
[0139] The membrane electrode assembly of the present invention includes an anode having a catalyst layer, a cathode having a catalyst layer, and the electrolyte membrane disposed between the anode and the cathode.
[0140] The membrane electrode assembly of the present invention includes the above-mentioned electrolyte membrane and can therefore be applied to a solid polymer water electrolysis device. The solid polymer water electrolysis device obtained by using the membrane electrode assembly has a low electrolysis voltage and excellent hydrogen recovery efficiency.
[0141] Hereinafter, an example of the membrane electrode assembly of the present invention will be described with reference to the drawings.
[0142] Figure 1 The membrane electrode assembly 10 includes an anode 13 having a catalyst layer 11 and a gas diffusion layer 12, a cathode 14 having a catalyst layer 11 and a gas diffusion layer 12, and an electrolyte membrane 15 disposed between the anode 13 and the cathode 14 in a state of contacting the catalyst layer 11.
[0143] Specific examples of the catalyst layer 11 include a layer containing a catalyst and a polymer having an ion exchange group.
[0144] Specific examples of the catalyst include: a supported catalyst in which a catalyst containing platinum, a platinum alloy, or platinum having a core-shell structure is supported on a carbon support; an iridium oxide catalyst; and a catalyst containing an alloy containing iridium oxide or iridium oxide having a core-shell structure. As a carbon support, carbon black powder can be cited.
[0145] Examples of the polymer having an ion exchange group include fluorine-containing polymers having an ion exchange group.
[0146] The gas diffusion layer 12 has the function of uniformly diffusing the gas in the catalyst layer and the function of serving as a current collector. Specific examples of the gas diffusion layer include carbon paper, carbon cloth, carbon felt, and a titanium porous body (specifically, a sintered body of titanium particles or fibers, etc.).
[0147] In order to prevent the generated gas from adhering, the gas diffusion layer may be subjected to water-repellent or hydrophilic treatment using PTFE or the like, or may be hydrophilicized using a polymer having an ion exchange group or the like.
[0148] Figure 1 The membrane electrode assembly includes the gas diffusion layer 12, but the gas diffusion layer is an optional component and may not be included in the membrane electrode assembly.
[0149] The electrolyte membrane 15 is an electrolyte membrane (solid polymer electrolyte membrane) containing the above-mentioned polymer electrolyte.
[0150] Specific examples of methods for manufacturing membrane electrode assemblies include: a method in which a catalyst layer is formed on an electrolyte membrane and the resulting assembly is further clamped by a gas diffusion layer; and a method in which a catalyst layer is formed on a gas diffusion layer to form an electrode (anode, cathode), and the electrolyte membrane is clamped by the electrodes.
[0151] The catalyst layer can be produced by applying a catalyst layer-forming coating liquid to a predetermined position and drying it as needed. The catalyst layer-forming coating liquid is a liquid obtained by dispersing a polymer having an ion exchange group and a catalyst in a dispersion medium.
[0152] [Solid polymer water electrolysis device]
[0153] The solid polymer water electrolysis device of the present invention includes the above-mentioned membrane electrode assembly.
[0154] Since the solid polymer water electrolysis device of the present invention includes the membrane electrode assembly described above, the electrolysis voltage is low and the hydrogen recovery efficiency is excellent.
[0155] In addition to using the above-mentioned membrane electrode assembly, the solid polymer water electrolysis device only needs to have a known structure, and examples thereof include a method having the following components: an electrolytic cell for setting up the membrane electrode assembly, a water supply means for supplying water to the anode side, a water recovery means for recovering excess water, a gas recovery means for recovering the generated hydrogen gas, etc., a power supply unit for applying voltage, etc.
[0156] In a solid polymer water electrolysis device, a voltage is applied between the anode and cathode of the membrane electrode assembly, and water is supplied to the anode side. The water supplied to the anode side is decomposed to generate hydrogen ions and oxygen. The generated hydrogen ions move to the cathode side via the solid polymer electrolyte membrane, where they combine with electrons to generate hydrogen.
[0157] Example
[0158] Hereinafter, the present invention will be described in detail by giving examples. Examples 6-1 to 6-6 and 7-1 to 7-6 are embodiments, and Examples 6-7 to 6-21 and 7-7 to 7-21 are comparative examples. However, the present invention is not limited to these examples. It should be noted that the compounding amount of each component in the table described below represents a mass basis.
[0159] [ 1 H-NMR]
[0160] 1 H-NMR was measured at a frequency of 300.4 MHz and a chemical shift standard of tetramethylsilane. As a solvent, CD3CN was used unless otherwise specified. The product was quantitatively determined according to 1 The analysis was performed based on the results of H-NMR analysis and the amount of the internal standard sample (1,3-bis(trifluoromethyl)benzene) added.
[0161] [ 19 F-NMR]
[0162] 19 F-NMR was measured under the conditions of frequency: 282.7 MHz, solvent: CD3CN, chemical shift standard: CFCl3. The product was quantitatively determined according to 19 The analysis was performed based on the results of F-NMR analysis and the amount of the internal standard sample (1,3-bis(trifluoromethyl)benzene) added.
[0163] [ 13 C-NMR]
[0164] 13 C-NMR was measured under the conditions of frequency: 75.5 MHz, chemical shift standard: tetramethylsilane. Unless otherwise specified, CD3CN was used as the solvent.
[0165] [Ion exchange capacity]
[0166] The film of polymer F or polymer F' is vacuum dried at 120°C for 12 hours. After measuring the mass of the dried polymer film, the polymer film is immersed in a 0.85 mol / g sodium hydroxide solution (solvent: water / methanol = 10 / 90 (mass ratio)) at 60°C for more than 72 hours to hydrolyze the group represented by -SO2F. The ion exchange capacity of polymer F or polymer F' is determined by back titrating the hydrolyzed sodium hydroxide solution with 0.1 mol / L hydrochloric acid. In this specification, the ion exchange capacity of polymer H or polymer H' as a polymer electrolyte is recorded as the same as the ion exchange capacity measured using polymer F or polymer F' as a precursor.
[0167] [Proportion of each unit]
[0168] The ratio of each unit in the polymer F or the polymer F' is calculated from the ion exchange capacity of the polymer F or the polymer F'.
[0169] The ratio of each unit in polymer H or polymer H' is the same as the ratio of the corresponding unit in polymer F or polymer F'.
[0170] [Hydrogen permeability coefficient]
[0171] The hydrogen permeability coefficient of a film (film thickness 25 μm) formed of polymer H or polymer H' as a polymer electrolyte was measured according to "Annex B (regulations) Test method based on gas chromatography" described in JIS K7126-2:2006 "Plastics - Films and sheets - Gas permeability test method - Part 2: Isobaric method" (corresponding international standard: ISO 15105-2:2003). As a measuring device, a gas permeability measuring device (GTR-100XFAG manufactured by GTR TEC Co., Ltd.) was used.
[0172] The effective penetration area is 9.62cm 2 The film formed of polymer H or polymer H' is maintained at 80°C, and hydrogen gas adjusted to 10% relative humidity is circulated to the first surface at 30 mL / min, and argon gas adjusted to 10% relative humidity is circulated to the second surface at 30 mL / min. The hydrogen gas gradually permeating into the argon gas is detected by gas chromatography, and the hydrogen permeation amount converted to a volume at 25°C and 1 atmosphere is calculated. Using the obtained hydrogen permeation amount, the hydrogen permeation amount per 1 cm 2 The hydrogen permeability coefficient is the value obtained by converting the membrane area and the gas permeability per second per 1 cmHg of the pressure difference of the permeating gas into a membrane thickness of 1 cm. It should be noted that the reference size and thickness of the membrane used in the calculation were measured under the conditions of temperature: 23°C and relative humidity: 50%RH.
[0173] [Membrane resistance and conductivity]
[0174] A substrate having four-terminal electrodes arranged at intervals of 5 mm was placed in close contact with a solid polymer electrolyte membrane having a width of 5 mm. The resistance value (membrane resistance value) of the solid polymer electrolyte membrane was measured by the known four-terminal method under constant temperature and humidity conditions of 80°C and 50% RH, with an alternating current of 10 kHz and a voltage of 1 V, and the conductivity was calculated.
[0175] [Moisture content]
[0176] After immersing the film formed by polymer H or polymer H' (film thickness 25 μm) in warm water at 80°C for 16 hours, cool it until the water temperature reaches below 25°C. Take out the film formed by polymer H or polymer H', wipe off the water attached to the surface of the film with filter paper, and measure the mass W1 of the film formed by polymer H or polymer H'. Dry the film formed by polymer H or polymer H' in a glove box with a nitrogen atmosphere for more than 48 hours, and then measure the mass W2 of the film formed by polymer H or polymer H' in the glove box. The water content (mass basis) is calculated by the following formula I.
[0177] Moisture content (%) = (W1-W2) / W2×100 Formula I
[0178] [Hydrogen leakage]
[0179] The amount of hydrogen leakage from the cathode side to the anode side through the solid polymer electrolyte membrane of the membrane electrode assembly was quantified in the form of the oxidation current value of hydrogen on the anode side by linear sweep voltammetry. The test was carried out as follows: Hydrogen (0.05 mL / min) and nitrogen (0.2 mL / min) were supplied to the cathode and anode respectively at normal pressure, and the potential on the anode side was scanned from 0.05 V to 0.5 V at a scan rate of 0.5 mV / sec with the cathode side as the reference electrode under the conditions of the cell temperature: 80°C and the relative humidity of hydrogen and nitrogen: 100% RH. In the obtained relationship between the current density and the potential, the intercept value of the linear approximation in the range of 0.4 to 0.5 V was used as the hydrogen leakage current value, and the evaluation was performed according to the following criteria. The smaller the hydrogen leakage current value, the better the hydrogen recovery efficiency of the solid polymer water electrolysis device.
[0180] ○: Hydrogen leakage current value is 0.15mA / cm 2 the following.
[0181] ×: Hydrogen leakage current value exceeds 0.15 mA / cm 2 .
[0182] [Electrolysis voltage]
[0183] The membrane electrode assembly was heat treated at 150° C. for 15 minutes and then mounted on a water electrolysis evaluation jig EH50-25 (manufactured by Greenlight Innovation Co., Ltd.).
[0184] Next, first, in order to fully hydrate the solid polymer electrolyte membrane and both electrode ionomers, pure water at 80°C and a conductivity of 1.0 μS / cm or less was supplied to the anode and cathode sides at a flow rate of 50 mL / min for 12 hours. Thereafter, the cathode side was purged with nitrogen.
[0185] After nitrogen purging, pure water with a conductivity of 1.0 μS / cm or less and a temperature of 80°C was supplied to the anode side at a flow rate of 50 mL / min. The back pressure was set to 100 kPaG for both the anode and cathode. A high current potentiometer / galvanostat HCP-803 (manufactured by Bio-Logic) was used to adjust the current density at 0 to 32 A (current density of 0 to 2 A / cm 2 ) range, the current was increased by 2.5 A at a time. In each stage, the current was maintained for 5 minutes, and the current was evaluated according to the following criteria: 32 A (current density 2 A / cm 2 ) when the electrolysis voltage is
[0186] ○: Less than 1.63V
[0187] ×: 1.63V or above
[0188] [film thickness]
[0189] The solid polymer electrolyte membrane was measured using a digital indicator (IDC112XB manufactured by MITUTOYO Co., Ltd.), and the average membrane thickness was obtained by taking the arithmetic average of the membrane thickness at any six points. The membrane thickness was measured at a temperature of 23° C. and a relative humidity of 50% RH.
[0190] [TQ value]
[0191] Using a flow tester (Shimadzu Corporation, CFT-500A) equipped with a nozzle of 1 mm in length and 1 mm in inner diameter, polymer F or F' was melt-extruded at an extrusion pressure of 2.94 MPa (gauge pressure) while changing the temperature. The extrusion volume of polymer F or F' reaching 100 mm 3 / second temperature (TQ value). The higher the TQ value, the larger the molecular weight of the polymer.
[0192] [Abbreviation]
[0193] TFE: tetrafluoroethylene,
[0194] PSVE: CF2=CFOCF2CF(CF3)OCF2CF2SO2F,
[0195] P2SVE: a monomer represented by the following formula m32-1,
[0196] sPSVE: CF2=CFOCF2CF2SO2F,
[0197] PFtBPO: (CF3)3COOC(CF3)3,
[0198] AIBN: (CH3)2C(CN)N=NC(CH3)2(CN)、
[0199] V-601: CH3OC(O)C(CH3)2-N=NC(CH3)2C(O)OCH3、
[0200] PFB: CF2CF2CF2C(O)OOC(O)CF2CF2CF3,
[0201] HFC-52-13p: CF3(CF2)5H,
[0202] HFE-347pc-f: CF3CH2OCF2CF2H,
[0203] HCFC-225cb:CClF2CF2CHClF,
[0204] HCFC-141b: CH3CCl2F.
[0205]
[0206] [Example 1]
[0207] <Example 1-1>
[0208] In a 2L four-necked flask equipped with a stirrer, a condenser, a thermometer, and a dropping funnel, 560 g of chlorosulfonic acid was placed under nitrogen sealing. The flask was cooled in an ice bath, and a mixture of 139.5 g of compound 1-1 and 478.7 g of dichloromethane was added dropwise over 20 minutes while maintaining the internal temperature below 20°C. Heat release and gas generation were observed during the dropwise addition. After the dropwise addition was completed, the flask was placed in an oil bath, and the reaction was carried out for 7 hours while maintaining the internal temperature at 30-40°C. The reaction was carried out while gas was generated, and a white solid was precipitated. After the reaction, the pressure in the flask was reduced to distill off the dichloromethane. A pale yellow white solid remained in the flask. By 1 As a result of H-NMR analysis of the solid, it was confirmed that compound 2-1 was generated.
[0209]
[0210] NMR spectrum of compound 2-1;
[0211] 1 H-NMR (solvent: D2O): 4.27 ppm (-CH2-, 4H, s).
[0212] 13 C-NMR (solvent: D2O): 62.6 ppm (-CH2-), 195.3 ppm (C=O).
[0213] <Example 1-2>
[0214] The compound 2-1 obtained in Example 1-1 was not isolated and was directly used in the next reaction. 2049 g of thionyl chloride was added to the flask of Example 1-1. The flask was heated to 80°C and refluxed for 15 hours. As the reaction proceeded, the reflux temperature rose from 52°C to 72°C. Gas generation was confirmed during the reaction. The point where compound 2-1 was completely dissolved and gas generation ended was set as the reaction endpoint. The reaction solution was transferred to a 2L detachable flask, the gas phase was sealed with nitrogen and naturally cooled for 9 hours. As a result, a dark brown solid was precipitated in the detachable flask. Unreacted thionyl chloride was removed by decantation. Toluene was added to wash the precipitated solid, and the toluene was removed again by decantation. Toluene washing was carried out a total of 3 times, and the total amount of toluene used was 1207 g. The precipitated solid was dried at 25°C for 71 hours under a nitrogen flow. The dried solid was recovered and passed through 1 As a result of H-NMR analysis, it was confirmed that 356.5 g of compound 3-1 with a purity of 96.2% was obtained. The yield based on compound 1-1 was 56.0%.
[0215]
[0216] NMR spectrum of compound 3-1;
[0217] 1 H-NMR: 5.20ppm (-CH2-, 4H, s).
[0218] 13 C-NMR: 72.3ppm (-CH2-), 184.6ppm (C=O).
[0219] <Example 1-3>
[0220] In a 1L four-necked flask equipped with a stirrer, a condenser, and a thermometer, 90.0g of compound 3-1 and 750mL of acetonitrile were placed under nitrogen sealing. The flask was cooled in an ice bath, and 110.3g of potassium bifluoride was added while stirring. A slight exotherm occurred with the addition. The ice bath was changed to a water bath, and the reaction was carried out for 62 hours while maintaining the internal temperature at 15-25°C. As the reaction proceeded, a fine white solid was generated. The reaction solution was transferred to a pressure filter to filter out the unreacted potassium bifluoride and the product. Acetonitrile was added to the filter, and the filtered solid was washed until the filtrate became transparent, and the washing liquid was recovered. The acetonitrile was distilled off the filtrate and the washing liquid using an evaporator. 950mL of toluene was added to the dried and remaining solid, and the solid was dissolved in toluene by heating to 100°C. The dissolved solution was naturally filtered to remove the undissolved components. The filtrate was transferred to a 1L separable flask, the gas phase was sealed with nitrogen and cooled naturally for 14 hours. As a result, light brown needle-shaped crystals were precipitated in the separable flask. The crystals were washed with toluene and dried at 25°C for 30 hours under a nitrogen stream. The dried solid was recovered and 1 H-NMR and 19 As a result of F-NMR analysis, it was confirmed that 58.1 g of compound 4-1 with a purity of 97.6% was obtained. The yield based on compound 3-1 was 72.3%.
[0221]
[0222] NMR spectrum of compound 4-1;
[0223] 1 H-NMR: 4.97ppm (-CH2-, 4H, d, J=3.1Hz).
[0224] 19 F-NMR: 62.4ppm (-SO2F, 2F, t, J=3.1Hz).
[0225] 13 C-NMR: 60.7ppm (-CH2-), 184.9ppm (C=O).
[0226] <Example 1-4>
[0227] In a 200mL nickel autoclave, 9.93g of compound 4-1 and 89.7g of acetonitrile were placed. The autoclave was cooled, and nitrogen was supplied at a flow rate of 6.7L / hr while the internal temperature was maintained at 0-5°C, and the reaction solution was bubbled for 1 hour. While the temperature of the reaction solution was maintained at 0-5°C, a mixed gas of fluorine gas and nitrogen (mixing ratio = 10.3 mol% / 89.7 mol%) was introduced at a flow rate of 6.7L / hr for 6 hours. Nitrogen was supplied again at a flow rate of 6.7L / hr, and the reaction solution was bubbled for 1 hour. 103.2g of the reaction solution was recovered from the autoclave. By 19 The reaction solution was quantitatively analyzed by F-NMR, and as a result, it was confirmed that the solution contained 8.4% by mass of compound 5-1. The reaction yield based on compound 4-1 was 66%.
[0228]
[0229] NMR spectrum of compound 5-1;
[0230] 19 F-NMR: -104.1ppm (-CF2-, 4F, s), 45.8ppm (-SO2F, 2F, s).
[0231] <Example 1-5>
[0232] In a 200mL nickel autoclave, 19.9g of compound 4-1 and 85.6g of acetonitrile were added. The autoclave was cooled, and nitrogen was supplied at a flow rate of 6.7L / hr while the internal temperature was maintained at 0-5°C, and the reaction solution was bubbled for 1 hour. While the temperature of the reaction solution was maintained at 0-5°C, a mixed gas of fluorine gas and nitrogen (mixing ratio = 10.3 mol% / 89.7 mol%) was introduced at a flow rate of 16.4L / hr for 6.5 hours. Nitrogen was supplied again at a flow rate of 6.7L / hr, and the reaction solution was bubbled for 1 hour. 109.6g of the reaction solution containing compound 5-1 was recovered from the autoclave.
[0233] <Example 1-6>
[0234] In a 200mL nickel autoclave, 20.1g of compound 4-1 and 80.1g of acetonitrile were added. The autoclave was cooled, and nitrogen was supplied at a flow rate of 6.7L / hr while the internal temperature was maintained at 0-5°C, and the reaction solution was bubbled for 1 hour. While the temperature of the reaction solution was maintained at 0-5°C, a mixed gas of fluorine gas and nitrogen (mixing ratio = 20.0 mol% / 80.0 mol%) was introduced at a flow rate of 8.4L / hr for 6 hours. Nitrogen was supplied again at a flow rate of 6.7L / hr, and the reaction solution was bubbled for 1 hour. 107.1g of the reaction solution containing compound 5-1 was recovered from the autoclave.
[0235] <Example 1-7>
[0236] In a 50 mL four-necked flask equipped with a stirrer, a condenser, a thermometer, and a dropping funnel, 1.65 g of potassium fluoride and 7.8 mL of diethylene glycol dimethyl ether (diglyme) were placed. While the flask was cooled and stirred in an ice bath to keep the internal temperature at 0-10°C, 8.43 g of the reaction solution obtained in Example 1-4 was added dropwise using a plastic syringe. Strong heat release was confirmed, and the addition required 15 minutes. After the addition was completed, the ice bath was replaced with a water bath, and the reaction was carried out at 15-20°C for 1 hour. After cooling in an ice bath again, 6.56 g of compound 6-1 was added dropwise from a dropping funnel while keeping the temperature of the reaction solution at 0-10°C. After the addition was completed, the ice bath was replaced with a water bath, and the reaction was carried out at 20-25°C for 3.5 hours. The by-product solids were removed from the reaction solution by suction filtration, and the filtrate was recovered. The filtered residual solids were washed with an appropriate amount of acetonitrile, and the washing liquid was mixed with the filtrate. By 19 37.1 g of the filtrate was quantitatively analyzed by F-NMR, and it was confirmed that the filtrate contained 2.04% by mass of compound 7-1. The reaction yield based on compound 4-1 was 46.6%.
[0237]
[0238] NMR spectrum of compound 7-1;
[0239] 19 F-NMR: -191.5ppm (CF2=CF-, 1F, ddt, J=116, 38, 14Hz), -133.8ppm (-O-CF-, 1F, tt, J=21.3, 6.1Hz), -103.1ppm (-CF2-SO2F, 4F, m), -101. 5ppm (CF2=CF-, 1F, ddt, J=116, 49, 27Hz), -87.6ppm (CF2=CF-, 1F, ddt, J=49, 38, 7Hz), -67.5ppm (-CF2-O-, 2F, m), 46.8ppm (-SO2F, 2F, s).
[0240] <Example 1-8>
[0241] Into a 500mL four-necked flask equipped with a stirrer, a condenser, a thermometer, and a dropping funnel, 36.6g of potassium fluoride and 125.6g of acetonitrile were placed. While the flask was cooled in an ice bath and stirred to maintain the internal temperature at 0-10°C, 79.8g of the reaction solution obtained in Example 1-5 was added dropwise using a plastic dropping funnel. Strong heat release was confirmed, and the addition required 23 minutes. After the addition was completed, the ice bath was replaced with a water bath, and the reaction was carried out at 20-30°C for 5.5 hours. The flask was cooled in an ice bath again, and 146.0g of compound 6-1 was added dropwise from the dropping funnel while maintaining the temperature of the reaction solution at 0-10°C. After the addition was completed, the ice bath was replaced with a water bath, and the reaction was carried out at 15-25°C for 16 hours. Suction filtration was performed in the same manner as in Example 1-7, and the reaction mixture was filtered through 19 The obtained filtrate 412.3 g was quantitatively analyzed by F-NMR, and the result confirmed that it contained 3.93% by mass of compound 7-1. The reaction yield based on compound 4-1 was 55.9%. The filtrate was subjected to reduced pressure distillation, thereby isolating compound 7-1 in the form of a boiling point 97.2°C / 10kPa fraction. The gas chromatography purity was 98.0%.
[0242] <Example 1-9>
[0243] Into a 50 mL four-necked flask equipped with a stirrer, a condenser, a thermometer, and a dropping funnel, 3.70 g of potassium fluoride and 10.9 g of acetonitrile were placed. While cooling the flask in an ice bath and stirring to maintain the internal temperature at 0-10°C, 10.2 g of the reaction solution obtained in Example 1-6 was added dropwise using a plastic syringe. Strong heat release was observed, and the addition required 8 minutes. After the addition was completed, the ice bath was replaced with a water bath, and the reaction was carried out at 20-30°C for 3 hours. Cooling was performed again in an ice bath, and 14.6 g of compound 6-1 was added dropwise from the dropping funnel while maintaining the temperature of the reaction solution at 0-10°C. After the addition was completed, the ice bath was replaced with a water bath, and the reaction was carried out at 15-25°C for 17 hours. Suction filtration was performed in the same manner as in Example 1-7, and the reaction mixture was filtered through 19 F-NMR quantitative analysis of 55.9 g of the obtained filtrate confirmed that it contained 4.77% by mass of compound 7-1. The reaction yield based on compound 4-1 was 69.6%. In addition, the reaction yield based on compound 1-1 (the reaction yield in the entire monomer synthesis step) was 28.2%.
[0244] [Example 2]
[0245] <Example 2-1>
[0246] 70.0 g of compound 7-1 was added to an autoclave (internal volume 100 mL, made of stainless steel), cooled with liquid nitrogen and degassed. 2.53 g of TFE was introduced into the autoclave, and the internal temperature was heated in an oil bath until the internal temperature reached 100°C. The pressure at this time was 0.29 MPaG (gauge pressure). A mixed solution of 36.3 mg of PFtBPO and 2.58 g of HFC-52-13p as a polymerization initiator was pressed into the autoclave. Nitrogen was then introduced from the injection line to completely squeeze the injection liquid into the injection line. Through this operation, the TFE in the gas phase was diluted, resulting in an increase in pressure to 0.56 MPaG. TFE was continuously added while maintaining the pressure at 0.56 MPaG to carry out polymerization. After 9.5 hours and when the amount of TFE added was 4.03 g, the autoclave was cooled to stop the polymerization and the gas in the system was purged. After the reaction solution was diluted with HFC-52-13p, HFE-347pc-f was added to aggregate the polymer and filtered. Thereafter, the operation of stirring the polymer in HFC-52-13p and reaggregating it in HFE-347pc-f was repeated twice. Vacuum drying was performed at 120°C to obtain a copolymer of TFE and compound 7-1, namely polymer F-1. The various physical properties of the obtained polymer F-1 were measured. The results are shown in Table 1.
[0247] <Example 2-2>
[0248] The conditions of Example 2-1 were changed as shown in Table 1. In Example 2-2, the initial charging of TFE was not performed. Instead, after heating to the polymerization temperature, TFE was blown in until the pressure before nitrogen dilution recorded in Table 1 was reached. Other than that, the same operation as in Example 2-1 was performed to obtain polymer F-2. The above-mentioned various physical properties were measured using the obtained polymer F-2. The results are shown in Table 1.
[0249] [Table 1]
[0250]
[0251] [Example 3]
[0252] <Example 3-1>
[0253] Using polymer F-1, a film of polymer H-1 was obtained by the following method.
[0254] The polymer F-1 was press-formed at a temperature 10°C higher than the TQ value and 4MPa (gauge pressure) to obtain a film of the polymer F-1. The film of the polymer F-1 was immersed in an alkaline aqueous solution A (potassium hydroxide / water = 20 / 80 (mass ratio)) at 80°C for 16 hours to hydrolyze -SO2F of the polymer F-1 and convert it into -SO3K. The polymer film was then immersed in a 3 mol / L hydrochloric acid aqueous solution at 50°C for 30 minutes, and then immersed in ultrapure water at 80°C for 30 minutes. A total of 5 cycles of immersion in an aqueous hydrochloric acid solution and immersion in ultrapure water were performed to convert -SO3K of the polymer into -SO3H. Washing with ultrapure water was repeated until the pH of the water in which the polymer film was immersed became 7. The polymer film was clamped with filter paper and air-dried to obtain a film of polymer H-1.
[0255] <Example 3-2>
[0256] A film of polymer H-2 was obtained in the same manner as in Example 3-1 except that polymer F-2 was used instead of polymer F-1 and alkali aqueous solution C (potassium hydroxide / methanol / water=15 / 20 / 65 (mass ratio)) was used instead of alkali aqueous solution A.
[0257] [Example 4]
[0258] <Example 4-1>
[0259] Into a Hastelloy alloy autoclave with an internal volume of 230 mL, 123.8 g of PSVE, 35.2 g of HCFC-225cb, and 63.6 mg of AIBN were added, and the mixture was cooled with liquid nitrogen and degassed. The temperature was raised to 70°C, TFE was introduced into the system, and the pressure was maintained at 1.14 MPa (gauge pressure). TFE was continuously added to keep the pressure constant at 1.14 MPa (gauge pressure). After 7.9 hours, when the amount of TFE added was 12.4 g, the autoclave was cooled, and the gas in the system was purged to terminate the reaction. After diluting the polymer solution with HCFC-225cb, HCFC-141b was added and aggregated. After washing with HCFC-225cb and HCFC-141b, the mixture was dried to obtain 25.1 g of polymer F'-1, which is a copolymer of TFE and PSVE. The results are shown in Table 2.
[0260] <Example 4-2~Example 4-3>
[0261] TFE and sPSVE or P2SVE were copolymerized in the same manner as in Example 4-1 except that the conditions of Example 4-1 were changed as shown in Table 2 to obtain polymers F'-2 to F'-3. The results are shown in Tables 3-1 and 3-2.
[0262] [Table 2]
[0263]
[0264] [Example 5]
[0265] <Example 5-1>
[0266] A film of polymer H'-1 was obtained in the same manner as in Example 3-1 except that polymer F'-1 was used instead of polymer F-1.
[0267] <Example 5-2>
[0268] A film of polymer H'-2 was obtained in the same manner as in Example 3-1 except that polymer F'-2 was used instead of polymer F-1.
[0269] <Example 5-3>
[0270] A film of polymer H'-3 was obtained in the same manner as in Example 3-1 except that polymer F'-3 was used instead of polymer F-1.
[0271] [Example 6]
[0272] <Example 6-1>
[0273] 4.3 g of a thinly cut polymer H-1 film and 75 g of ultrapure water were added to a 100 mL polytetrafluoroethylene (PTFE) container and heated at 200° C. for 24 hours. The contents were transferred to a PTFE cylinder and air-dried for 64 hours at 30° C. under a nitrogen atmosphere. The dried polymer H-1 was transferred to a 200 mL glass autoclave and 21.4 g of a mixed solvent of ultrapure water / ethanol (50 / 50 (mass ratio)) was added. After stirring at 110° C. for 25 hours, 3.87 g of ultrapure water was added for dilution. After stirring at 90° C. for 5 hours, the mixture was cooled naturally and filtered using a pressure filter (filter paper: ADVANTEC TOYO, PF040) to obtain 31.9 g of a liquid composition S-1 in which polymer H-1 was dispersed in a mixed solvent.
[0274] The liquid composition S-1 was coated on a 100 μm ethylene-tetrafluoroethylene copolymer (ETFE) sheet by a die coater to form a film, which was dried at 80° C. for 15 minutes and then heat-treated at 185° C. for 30 minutes to obtain a solid polymer electrolyte membrane 1 formed of a film of polymer H as an electrolyte. It should be noted that the coating amount of the liquid composition was adjusted so that the film thickness of the solid polymer electrolyte membrane would be the value described in Tables 3-1 to 3-2. The results are shown in Table 3-1.
[0275] <Example 6-2~Example 6-21>
[0276] Use polymer H or polymer H' described in Tables 3-1 to 3-2 instead of polymer H-1 to prepare a liquid composition, and adjust the coating amount of the liquid composition so that the film thickness of the solid polymer electrolyte membrane becomes the value described in Tables 3-1 to 3-2. Otherwise, the same operations are performed as in Example 6-1 to obtain solid polymer electrolyte membranes 2 to 21 formed by films of polymer H or H'.
[0277] It should be noted that in Tables 3-1 and 3-2, polymer H'-4 refers to NAFION (registered trademark) 117 (manufactured by DuPont. An electrolyte membrane with a thickness of 180 μm formed by a perfluoropolymer containing TFE units and PSVE units). Polymer H'-5 refers to NAFION (registered trademark) 115 (manufactured by DuPont. An electrolyte membrane with a thickness of 130 μm formed by a perfluoropolymer containing TFE units and PSVE units). Polymer H'-6 refers to NAFION (registered trademark) 212 (manufactured by DuPont. An electrolyte membrane with a thickness of 50 μm formed by a perfluoropolymer containing TFE units and PSVE units).
[0278] The results are shown in Tables 3-1 and 3-2.
[0279] [Table 3-1]
[0280]
[0281] [Table 3-2]
[0282]
[0283] In Tables 3-1 and 3-2, “2.10E-09” and the like are abbreviations of exponential notation. As a specific example, “2.10E-09” means “2.10×10 -9 ” The same applies to Table 4-1 and Table 4-2 described later.
[0284] [Example 7]
[0285] <Example 7-1>
[0286] A polymer (ion exchange capacity: 1.10 milliequivalents / g dry resin) obtained by copolymerizing TFE and PSVE and then hydrolyzing and acid-treating to obtain an acid-type polymer was dispersed in a solvent of water / ethanol = 40 / 60 (mass %) at a solid content concentration of 25.8% to obtain a dispersion (hereinafter also referred to as "dispersion X"). To the obtained dispersion X (19.0 g) were added ethanol (0.52 g) and water (3.34 g), and further, a 76 mass % iridium-containing quartz crystal with a specific surface area of 100 m 2 / g of iridium oxide catalyst (manufactured by Tanaka Precious Metals Co., Ltd.) (13.0g). The obtained mixture was treated with a planetary bead mill (rotation speed of 300rpm) for 30 minutes, and then water (4.49g) and ethanol (4.53g) were added, and then treated with a planetary bead mill (rotation speed of 200rpm) for 60 minutes to obtain an anode catalyst ink with a solid content concentration of 40% by mass.
[0287] Use an applicator to apply the anode catalyst ink with iridium to a concentration of 1.0 mg / cm 2 The anode catalyst layer was coated on an ETFE sheet in the manner of , dried at 80° C. for 10 minutes, and further heat treated at 150° C. for 15 minutes to obtain an anode catalyst layer decoration.
[0288] Water (59.4 g) and ethanol (39.6 g) were added to a supported catalyst (11 g) containing 46% by mass of platinum supported on carbon powder ("TEC10E50E" manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.), and mixed and pulverized using an ultrasonic homogenizer to obtain a catalyst dispersion.
[0289] A mixed solution (29.2 g) obtained by pre-mixing and kneading the dispersion X (20.1 g), ethanol (11 g) and ZEORORA-H (manufactured by ZEON Corporation, Japan) (6.3 g) was added to the catalyst dispersion. Furthermore, water (3.66 g) and ethanol (7.63 g) were added to the obtained dispersion, and mixed for 60 minutes using a paint mixer to adjust the solid content concentration to 10.0% by mass, thereby obtaining a cathode catalyst ink.
[0290] The cathode catalyst ink was applied to an ETFE sheet using a die coater, dried at 80°C, and further heat treated at 150°C for 15 minutes to obtain a platinum content of 0.4 mg / cm 2 Cathode catalyst layer decoration.
[0291] The surface of the anode catalyst layer decoration on which the anode catalyst layer is decorated faces one side of the solid polymer electrolyte membrane 1, and the surface of the cathode catalyst layer decoration on which the catalyst layer is decorated faces the other side of the electrolyte membrane. The anode catalyst layer, the solid polymer electrolyte membrane 1 and the cathode catalyst layer are joined by heating and pressing at a pressing temperature of 150°C, a pressing time of 10 minutes and a pressure of 3MPa. After the temperature is lowered to 70°C, the pressure is released and the decoration is taken out. The ETFE sheets of the anode catalyst layer decoration and the cathode catalyst layer decoration are peeled off to obtain an electrode with an area of 16cm 2 The obtained membrane electrode assembly was used to evaluate the electrolysis voltage and hydrogen leakage. The results are shown in Table 4-1.
[0292] <Example 7-2~Example 7-21>
[0293] A membrane electrode assembly for evaluation of electrolysis voltage and hydrogen leakage was prepared in the same manner as in Example 7-1 except that the solid polymer electrolyte membranes 2 to 21 listed in Tables 4-1 and 4-2 were used instead of the solid polymer electrolyte membrane 1 obtained in Example 6-1. The results are shown in Tables 4-1 and 4-2.
[0294] [Table 4-1]
[0295] Example 7-1 Example 7-2 Example 7-3 Example 7-4 Example 7-5 Example 7-6 Example 7-7 Example 7-8 Example 7-9 Example 7-10 Example 7-11 Types of solid polymer electrolyte membranes 1 2 3 4 5 6 7 B 9 10 11 Electrolysis voltage ○ ○ ○ ○ ○ ○ - × - × × Hydrogen leakage ○ ○ ○ ○ ○ ○ - ○ - ○ ×
[0296] [Table 4-2]
[0297] Example 7-12 Example 7-13 Example 7-14 Example 7-15 Example 7-16 Example 7-17 Example 7-18 Example 7-19 Example 7-20 Example 7-21 Types of solid polymer electrolyte membranes 12 13 14 15 16 17 18 19 20 21 Electrolysis voltage × ○ × × ○ ○ ○ × × ○ Hydrogen leakage × × × × × × × × × ×
[0298] In the above Table 4-1, the mark “-” in the electrolysis voltage and hydrogen leakage amount means that the solid polymer electrolyte membrane was damaged during the evaluation and could not be evaluated.
[0299] As shown in Tables 3-1 to 3-2 and Tables 4-1 to 4-2, if the hydrogen permeability coefficient under the conditions of temperature 80°C and relative humidity 10% is 2.4×10 -9 cm 3 cm / (s cm 2 ·cmHg) or less, and the membrane resistance value is 50 to 150 mΩ·cm under the conditions of temperature 80°C and relative humidity 50%. 2 By using a solid polymer electrolyte membrane, a solid polymer water electrolysis device with low electrolysis voltage and excellent hydrogen recovery efficiency can be obtained (Examples 6-1 to 6-6, Examples 7-1 to 7-6).
[0300] In contrast, when a solid polymer electrolyte membrane is used in which at least one of the hydrogen permeability coefficient and the membrane resistance value is outside the above-mentioned range, at least one of the electrolysis voltage or the hydrogen recovery efficiency of the solid polymer water electrolysis device obtained using the membrane is poor (Example 6-8, Example 6-10 to Example 6-21, Example 7-8, and Example 7-10 to Example 7-21).
[0301] In addition, it can be seen that: when using a solid polymer electrolyte membrane with a membrane resistance value smaller than the above-mentioned range, the solid polymer electrolyte membrane is damaged during the evaluation, and the evaluation of the electrolysis voltage and hydrogen leakage cannot be carried out, making it difficult to apply to solid polymer water electrolysis devices (Examples 6-7, 6-9, 7-7 and 7-9).
[0302] It should be noted that the entire contents of the specification, claims, drawings, and abstract of Japanese Patent Application No. 2019-036692 filed on February 28, 2019 are cited herein and incorporated as the disclosed contents of the present specification.
[0303] Industrial Applicability
[0304] 10 Membrane Electrode Assembly
[0305] 11 Catalyst layer
[0306] 12 Gas Diffusion Layer
[0307] 13 Anode
[0308] 14 Cathode
[0309] 15 Electrolyte membrane
Claims
1. A solid polymer electrolyte membrane, characterized in that: The polymer electrolyte has a hydrogen permeability of 2.4×10 -9 cm 3 cm / (s cm 2 cmHg) or less, The membrane resistance of the solid polymer electrolyte membrane is 50 to 150 mΩ·cm under the conditions of a temperature of 80° C. and a relative humidity of 50%. 2 , The solid polymer electrolyte membrane has a thickness of 70 μm or more and 120 μm or less. The polymer electrolyte is a perfluoropolymer having an acidic sulfonic acid group. The perfluoropolymer comprises perfluoro monomer units, The perfluoromonomer unit comprises at least one unit selected from the group consisting of a perfluorovinyl ether unit and a perfluoroallyl ether unit, The perfluoropolymer does not substantially contain at least one unit selected from the group consisting of a unit having a halogen atom other than a fluorine atom, a unit having a ring structure, and a unit having a crosslinked structure formed by a covalent bond.
2. The solid polymer electrolyte membrane according to claim 1, wherein The perfluoroallyl ether unit is a unit represented by formula A-1, In formula A-1, R F1 and R F2 Each is independently a perfluoroalkylene group having 1 to 3 carbon atoms.
3. The solid polymer electrolyte membrane according to claim 1, wherein The perfluoromonomer units further include tetrafluoroethylene units.
4. The solid polymer electrolyte membrane according to claim 2, wherein: The perfluoromonomer units further include tetrafluoroethylene units.
5. The solid polymer electrolyte membrane according to any one of claims 1 to 4, wherein The ion exchange capacity of the polymer electrolyte is 1.4 to 2.5 milliequivalents per gram of dry resin.
6. A membrane electrode assembly, characterized in that: The invention comprises: an anode having a catalyst layer, a cathode having a catalyst layer, and the solid polymer electrolyte membrane according to any one of claims 1 to 5 arranged between the anode and the cathode.
7. A solid polymer water electrolysis device, characterized in that: It comprises the membrane electrode assembly according to claim 6.
Citation Information
Patent Citations
Solid polymer type water electrolytic cell
JP1999021687A
Solid high molecular electrolytic fuel cell
JP2001176524A
Method for producing dispersion liquid containing sulfonic acid type perfluoro-copolymer
JP2005082749A
Manufacturing method of semiconductor light-emitting device and the semiconductor light-emitting device
JP2019036692A
Polymer containing fluorosulfonyl group or sulfonic acid group, method for producing same, and use of same
CN111051368A